Peter Brask, Karsten Friis-Jensen, Jens Glebe-Møller, Tage Hind, Minna Skafte Jensen, Anders Jørgensen, Sigurd Kværndrup, Jens Rahbek Rasmussen, Janne Risum og Bjarne Thorup Thomsen: Dansk litteratur historie, 2. Lærdom og magi. 1480-1620. 1984). 528 s. - Degn, Ole (Historie/Jyske Samlinger, 1987)
-